2020
DOI: 10.1371/journal.pgen.1009067
|View full text |Cite
|
Sign up to set email alerts
|

The DNA damage response is required for oocyte cyst breakdown and follicle formation in mice

Abstract: Mammalian oogonia proliferate without completing cytokinesis, forming cysts. Within these, oocytes differentiate and initiate meiosis, promoting double-strand break (DSBs) formation, which are repaired by homologous recombination (HR) causing the pairing and synapsis of the homologs. Errors in these processes activate checkpoint mechanisms, leading to apoptosis. At the end of prophase I, in contrast with what is observed in spermatocytes, oocytes accumulate unrepaired DSBs. Simultaneously to the cyst breakdown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 50 publications
0
33
0
Order By: Relevance
“…whereas the combined activity of CHK1 and CHK2 is required to reduce oocyte number and promote folliculogenesis in mice (Martínez-Marchal et al, 2020).…”
Section: The Pachytene Checkpointmentioning
confidence: 99%
See 1 more Smart Citation
“…whereas the combined activity of CHK1 and CHK2 is required to reduce oocyte number and promote folliculogenesis in mice (Martínez-Marchal et al, 2020).…”
Section: The Pachytene Checkpointmentioning
confidence: 99%
“…Intriguingly, the pachytene checkpoint can also affect subsequent germline development. In Drosophila , this pathway reduces the levels of the developmental regulator Gurken, leading to impaired egg chamber polarization ( Abdu et al, 2002 ), whereas the combined activity of CHK1 and CHK2 is required to reduce oocyte number and promote folliculogenesis in mice ( Martínez-Marchal et al, 2020 ).…”
Section: The Pachytene Checkpointmentioning
confidence: 99%
“…Recent GWAS studies identified CHEK2 as a major factor associated with ovarian aging and the onset of natural menopause in women (154,155). Animal model studies showed that this is due to a larger PMF reserve found in CHEK2-deficient mice (26,155,156). Furthermore, we showed that CHEK2deficient primordial oocytes are more resistant to DNA damage induced by radiation (26) and chemotherapy drugs (this study), and we expect that they will be resistant to other types of DNA damaging exposures.…”
Section: Discussionmentioning
confidence: 51%
“…In females, ATR has been implicated in detecting oocytes with DSBs and activating TAp63α ( Kim et al, 2019 ). Besides CHK2, another checkpoint kinase, CHK1 has also been found to mediate removal of damaged oocytes ( Martinez-Marchal et al, 2020 ; Rinaldi et al, 2020 ).…”
Section: Elimination Of Oocytes With Defective Dna Repair or Synapsismentioning
confidence: 99%